Examples of dramatic failures and their effectiveness in modern surgical disciplines: can we learn from our mistakes?. (11th June 2018) - Ball, Chad G; Grondin, Sean C; Pasieka, Janice L; Kirkpatrick, Andrew W; MacLean, Anthony R; Cantle, Paul; Dixon, Elijah; Schneider, Prism; Hamilton, Mark
Innovation can be variably defined, but when applied to healthcare is often considered to be the introduction of something new, whether an idea, method or device, into an unfilled void or needy environment. Despite the introduction of many positive surgical subspecialty altering concepts/devices however, epic failures are not uncommon. These failures can be dramatic in regards to both their human and economic costs. They can also be very public or more quiet in nature. As surgical leaders in our communities and advocates for patient safety and outcomes, it remains crucial that we meet new introductions in technology and patient care with a measured level of curiosity, skepticism and science-based conclusions. The aim of an expert committee was to identify the most dominant failures in technological innovation and/or dogmatic clinical beliefs within each major surgical subspecialty. In summary, this effort was pursued to highlight the past failures and remind surgeons to remain vigilant and appropriately skeptical with regard to the introduction of new innovations and clinical beliefs within our craft.